Republic of Lithuania : Financial System Stability Assessment; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Lithuania's catch-up toward the European average has been impressive. This success has been coupled with the emergence of macroeconomic imbalances. The dominance of foreign-owned banks in the banking system constitutes both a source of strength and risk. Although stress tests indicate that the banking system is reasonably resilient to macroeconomic shocks, existing capital buffers might not be sufficient to cope with low probability extreme events, and strengthening the capital would be advisable. The government implemented a regulatory framework for Nonbank Financial Institution (NBFI) and a pension reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet